Lactic Acid Bacteria Biosurfactant Role That Isolated from Human Breast Milk in Inhibit Eyes Pathogenic Bacteria - M.B. Muhsin, Yusra; Z. Majeed, Huda; Basim Mohammed, Basam; A.A. Mohammed, Salih (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Biosurfactants have a wide-range of applications due to their unique properties like specificity, not toxicity (from LAB) and relative ease of preparation. These properties hold promise of biosurfactants to increase breast milk benefit were isolated and described into Lactobacillus plantarum, Lactobacillus fermentum ,Lactococcuslactis, and Leuconostocmesenteroides.The degree of microbial destruction of disease, which promotes  the effective remediation of disease spreading.This paper presents a review of available research, methods and publications regarding Biosurfactant extraction from Lactic Acid bacteria isolated from human breast milk. 3 samples of human breast milk was provided, LAB were isolated and described, Biosurfactants recovery and surface activity were tested and extracted endo and extra cellular. In other side 26 samples from eye patients were ordered, diagnosed and their sensitivity to biosurfactant were studied. The results showed that 5 isolates of LAB from human breast milk were biosurfactant producer but L. plantarum was the more efficiency in surface activity. In other side, out of 26 eyes sample 18 were positive to pathogenic bacteria included E.coli (7), Klebseilla (5), Staphylococcus aureus(3)and S.epidermides (3).Extracellular Biosurfactanthad good effect against tested bacteria, but endocellular (extraction by normal method) had not any effect against any bacteria, whereas by solvents method were the more active against all tested bacteria. The results are promising enough to continue the quest for enhancement of inhibition growth of pathogenic bacteria with biosurfactant application (extracted extracellular by solvents) to look forward for biosurfactant as a solution of antibiotic resistance problem. In this study we concluded thatL. plantarum was the more effectiveness in biosurfactant surface activity and the extracellular biosurfactant by solvent method for extraction were better than endocellular and normal method of extraction.